From the crust to the cortical: The geochemistry of trace elements in human bone. (15th March 2019) - Harkness, Jennifer S.; Darrah, Thomas H.
Abstract: Trace element incorporation into human bone depends upon dietary, geological, and environmental inputs as well as biological processes that biopurify essential elements, while depleting nonessential or toxic elements. Thus, the trace element composition of human bones provides a geochemical archive of biological, environmental, anthropological, and/or geographic conditions that have occurred throughout an individual's life. While the majority of research has focused on the incorporation of a select subset of elements (i.e., Ca, F, Sr, Pb, K, Mg, Zn, Na), less information exists on the abundances of many other geologically informative trace elements and the processes that control their incorporation into human bone. In this study, we use ICP-MS to characterize the distribution of 36 trace elements in cortical bone tissues from femoral heads to investigate their incorporation into modern human bones. We propose a standard system for the evaluation of trace elements in human bone by normalizing trace element contents to bone mineral content (i.e., normalized concentrations of element X = (XN )bone = [X]/[Ca], where X is the measured abundance for a trace element of interest and Ca is the measured calcium content). Because Zn is known to be highly regulated by an individual's homeostatic processes, we compare trace element abundances to Zn concentrations to determine which elements are modified by homeostatic processes. Using this framework, we identify one subset of trace elements that correlates strongly to Zn consistent with homeostatic regulation and a second subset of elements that exhibits statistically insignificant correlations to Zn, which we infer as a lack of homeostatic regulation. While the first subset of elements experiences homeostatic regulation and therefore do not reflect dietary or environmental inputs, the second subset of trace elements can be linked to geographic location or dietary inputs. Ratios of incorporation (Ri  = ((XN )bone )/([X]/[Ca]UCC )) of trace elements into bone quantify the relative deviation for each trace element from the theoretical geological standard for average soil composition, which is assumed here to be equivalent to Upper Continental Crust (UCC). Rare earth elements (REEs) and oxyanions may provide the best proxy for geographical provenance studies.